Landscape user experiences of interspace and overhead agrivoltaics: A comparative analysis of two novel types of solar landscapes in the Netherlands - Biró-Varga, Kitti; Sirnik, Igor; Stremke, Sven (Energy research & social science, 2024)
As renewable energy adoption accelerates, solar power plants are being installed at a higher-than-ever rate, frequently occupying agricultural lands. Agrivoltaic systems integrate crop cultivation and electricity production on the same land, providing a solution for the otherwise competing land use demands between energy generation and food production. The implementation of agrivoltaic power plants, however, potentially impacts landscape quality, consequently raising concerns among local inhabitants and other landscape users. This study examines the effects of two types of agrivoltaic systems on landscape quality and how people perceive these transformed landscapes. Eleven landscape quality factors are assessed in a survey with residents from Culemborg and Wadenoijen, the Netherlands, to compare their landscape experience before and after the construction of agrivoltaic systems. The results indicate a decrease in the experiential value after the implementation of agrivoltaic systems, while the future value shows a slight increase. The use value – the third dimension of landscape quality - increases for the interspace agrivoltaics and declines for the overhead system. Environmental impacts, wildlife habitats as well as health and well-being are rated as the most important factors for the design and implementation of agrivoltaic systems by landscape users. Although respondents support farmers' involvement in the energy transition and the multifunctional character of agrivoltaics, they express concerns about the impact on wildlife and the decline in the attractiveness of the landscapes. This study suggests directions for further research on the landscape-energy nexus and provides recommendations for the development of landscape-inclusive agrivoltaic power plants. •Landscape quality of two types of agrivoltaic power plants are compared in a survey.•Interspace agrivoltaics was preferred over the overhead system.•Environmental impacts and wildlife habitats emerged as the most relevant factors.•Experiential value was perceived as declined by landscape users.•Future research should address local perceptions of agrivoltaics.